1999
DOI: 10.1016/s0002-9440(10)65304-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Innervation-Regulated Expression of the Intermediate Filament Protein Nestin at Neuromuscular and Myotendinous Junctions in Skeletal Muscle

Abstract: The intermediate filament proteins nestin, vimentin, and desmin show a specific temporal expression pattern during the development of myofibers from myogenic precursor cells. Nestin and vimentin are actively expressed during early developmental stages to be later down-regulated, vimentin completely and nestin to minimal levels, whereas desmin expression begins later and is maintained in mature myofibers, in which desmin participates in maintaining structural integrity. In this study we have analyzed the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 29 publications
(30 reference statements)
5
73
0
Order By: Relevance
“…Both of these antibodies were crossreactive with mouse, rat, and human CRF2R, allowing cross-species comparison. In addition, we attempted to localize the CRF2R to specific substructures in skeletal muscle using antibodies specific for proteins found in neurons (neurofilament and PGP9.5) (Krikler et al 1992;Nahirney and Ovalle 1993;Blumer et al 2001;Kawabuchi et al 2001), proteins found on blood vessel ( ␣ -smooth muscle actin) (Nora et al 1998), and proteins found at the myotendinous junction (tubulin and nestin) (Ralphs et al 1991;Yarnitzky et al 1997;Carlsson et al 1999;Vaittinen et al 1999). In addition, we used rhodamine-conjugated ␣ -bungarotoxin (Molecular Probes) to co-localize CRF2R staining to the neuromuscular junction.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these antibodies were crossreactive with mouse, rat, and human CRF2R, allowing cross-species comparison. In addition, we attempted to localize the CRF2R to specific substructures in skeletal muscle using antibodies specific for proteins found in neurons (neurofilament and PGP9.5) (Krikler et al 1992;Nahirney and Ovalle 1993;Blumer et al 2001;Kawabuchi et al 2001), proteins found on blood vessel ( ␣ -smooth muscle actin) (Nora et al 1998), and proteins found at the myotendinous junction (tubulin and nestin) (Ralphs et al 1991;Yarnitzky et al 1997;Carlsson et al 1999;Vaittinen et al 1999). In addition, we used rhodamine-conjugated ␣ -bungarotoxin (Molecular Probes) to co-localize CRF2R staining to the neuromuscular junction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the expression of nestin may be associated with an increase in cytoplasmic trafficking required for progenitor cells undergoing rapid rounds of division, interspersed with active interphase migration. These activities are hallmarks of the nestin-expressing cells found in early developing nerve and muscle systems (Lendahl et al, 1990;Sejersen and Lendahl, 1993;Kachinsky et al, 1995;Vaittinen et al, 1999) and in cells responding to the injury and regeneration of adult tissues (Frisen et al, 1995;Vaittinen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Clues regarding the identity of these cell type-specific factors come from our recent studies of the high-molecularweight proteins present in purified IF preparations of BHK-21 cells (Steinert et al, 1999). One of these has been identified as nestin, a protein known to be expressed in neuroepithelial cells and developing muscle cells (Lendahl et al, 1990;Sejersen and Lendahl, 1993;Kachinsky et al, 1995;Vaittinen et al, 1999). Nestin cannot form filaments on its own, but it can readily form copolymer IFs when combined with type III IF proteins such as vimentin both in vitro and in vivo (Marvin et al, 1998;Eliasson et al, 1999;Steinert et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Upon differentiation, nestin expression is down-regulated and replaced by other tissue-specific IF proteins, such as glial fibrillary acidic protein (GFAP) in astrocytes, neurofilaments in neurons, and desmin in muscle tissue, respectively. Interestingly, nestin expression is reinduced during various regenerative and degenerative conditions in the fully differentiated organism (6,7).…”
Section: The Intermediate Filament (If)mentioning
confidence: 99%